2012
DOI: 10.1109/tbcas.2012.2218105
|View full text |Cite
|
Sign up to set email alerts
|

A 4 <formula formulatype="inline"><tex Notation="TeX">$\mu{\rm W}/{\rm Ch}$</tex></formula> Analog Front-End Module With Moderate Inversion and Power-Scalable Sampling Operation for 3-D Neural Microsystems

Abstract: We report an analog front-end prototype designed in 0.25 μm CMOS process for hybrid integration into 3-D neural recording microsystems. For scaling towards massive parallel neural recording, the prototype has investigated some critical circuit challenges in power, area, interface, and modularity. We achieved extremely low power consumption of 4 μW/channel, optimized energy efficiency using moderate inversion in low-noise amplifiers (K of 5.98 × 10⁸ or NEF of 2.9), and minimized asynchronous interface (only 2 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Such a probe could, in principle, record from between 1000 to 5000 neurons and determine the three-dimensional position of both cell bodies and the main dendrites of each neuron. These technical improvements are within reach but will require high-density off-chip lead transfers, probably in conjunction with on-probe circuitry ( Al-Ashmouny et al, 2012 ; Bai and Wise, 2001 ; Perlin and Wise, 2010 ; Wise et al, 2004 ). We should emphasize that even slim-shank probes come at the expense of tissue damage, fractional displacement volume and associated disruption of physiological activity that needs to be carefully investigated ( Claverol-Tinture and Nadasdy, 2004 ; Polikov et al, 2005 ; Tsai et al, 2009 )…”
Section: Hardware Components For Large-scale Monitoring Of Neuronal Amentioning
confidence: 99%
“…Such a probe could, in principle, record from between 1000 to 5000 neurons and determine the three-dimensional position of both cell bodies and the main dendrites of each neuron. These technical improvements are within reach but will require high-density off-chip lead transfers, probably in conjunction with on-probe circuitry ( Al-Ashmouny et al, 2012 ; Bai and Wise, 2001 ; Perlin and Wise, 2010 ; Wise et al, 2004 ). We should emphasize that even slim-shank probes come at the expense of tissue damage, fractional displacement volume and associated disruption of physiological activity that needs to be carefully investigated ( Claverol-Tinture and Nadasdy, 2004 ; Polikov et al, 2005 ; Tsai et al, 2009 )…”
Section: Hardware Components For Large-scale Monitoring Of Neuronal Amentioning
confidence: 99%
“…This strategy leverages the fact that not all electrode sites may provide useful information after implantation [97, 101, 145] or that the necessary information can be obtained from a small subset of electrodes, although the useful electrode subset is not known a priori [118]. For example, Al-ashmouny et al reported a 128-input channel neural recording IC [2] with only 16 inputs selectively routed to the front-end amplifiers, therefore achieving power and area reduction. Another recent work by Lopez et al [77] adopted the same method and multiplexed 455 electrode inputs to 52 amplifiers.…”
Section: Background On Neural Recording Amplifiersmentioning
confidence: 99%
“…The front-end amplifiers operated at 1.8 V, while the supply voltage of the ADC and the backend digital blocks were reduced to 1 V to decrease the dynamic switching power. Similarly, Al-ashmouny et al [2] reported an implementation where the supply voltage of the ADC was made scalable according to the sampling rate, throttling the power consumption. Finally, the chip reported by Han et al [48] used 0.9 and 0.45 V supply domains for the amplification stage and ADC, respectively.…”
Section: Background On Neural Recording Amplifiersmentioning
confidence: 99%